Study of the correlation between the expression of nuclear factor kappa B and proliferation regulatory proteins and chronic superficial gastritis - Hu, Hui; Ma, Zhijian; Ren, Shouzhong; Xie, Yiqiang (Vojnosanitetski pregled, 2022)
Background/Aim. Cell proliferation and the regulation of protein expression play an important role in gastritis, but in chronic superficial gastritis (CSG), they are rarely reported. The aim of this study was to determine the relationship between the expression of nuclear factor kappa B (NF-κB) and regulatory proteins and the rat CSG. Methods. The CSG rat model was established artificially, by chemical agents and irregular diet. The expression of epidermal growth factor receptor (EGFR) and proliferating cell nuclear antigen (PCNA) in the gastric mucosa of CSG rats was measured by immunohistochemistry, while mRNA expression levels of NF-κB p65 were detected by in situ hybridization. Results. There was more obvious infiltration of inflammatory cells in the gastric mucosa of CSG rats than in that of control rats, and the inflammation score was significantly increased. The expression levels of PCNA, EGFR, and NF-κB p65 mRNA in the gastric mucosal cells of CSG model rats increased significantly. Correlation analysis showed that the inflammation score was positively correlated with the expression levels of NF-κB p65 mRNA and EGFR, while it presented no significant correlation with the expression level of PCNA. In addition, there was a significant positive correlation between NF-κB p65 mRNA and EGFR levels. Conclusion. High expression of NF-κB and EGFR plays an important role in the occurrence and progression of CSG, and it is significantly positively correlated with the degree of inflammation in the gastric mucosa. Therefore, changes in NF-κB and EGFR expression may be used as important indicators for the assessment of CSG; changes in their expression levels are helpful to assess the degree of gastric mucosal lesions and progression of CSG.